The Relationship Between Learning Styles and Multiple Intelligences among Malaysian Medical and health Sciences Students. - Wong, Rebecca S.Y (2017)
Most studies on learning styles (LS) and multiple intelligences (MI) have predominantly been conducted in a single institution. Comparative studies involving two or more medical schools are currently lacking and the correlation between LS and MI have not been sufficiently established. This study was a multidisciplinary and multi institutional study on the LS and MI of medical and health sciences students from three Malaysian universities using the VARK questionnaire and MI Inventory respectively. Differences in the mean VARK subscale scores and mean MI domain scores according to gender, race, first language, family income and academic achievements were analysed while age and the pre-university cumulative grade point average (CGPA) were correlated to these mean scores. The mean VARK subscale scores were also correlated to the mean MI domain scores. The most powerful indicator of LS and MI were determined using a path analysis. Both interdisciplinary and inter-institutional differences in LS and MI were observed. Overall, a majority of the students were unimodal learners. The most common type of learners was the reading/writing type whereas the kinesthetic subscale had the highest mean score. Regardless of disciplines and universities, all cohorts of students had the highest mean score in the intrapersonal domain and the lowest mean score in the verbal/linguistic domain. All demographic factors played a role in the learning preferences and MI to a varying extent, except for family income, which had no influence on LS. Learning preferences did not differ significantly between high and non-high achievers. However, statistical significant differences in the mean existential,kinesthetic and interpersonal domain scores existed between high and non-high achievers. Path analysis showed that the most powerful predictor of LS and MI was the first language and age respectively (combining all medical and health sciences students from University A), and gender and family income respectively (combining all Year 1 medical students from all three universities). A statistical significant correlation between all VARK subscales with at least one or more MI domains existed. Interestingly, none of the VARK subscales correlated to the interpersonal domain. The presence of interdisciplinary, inter-institutional and individual differences implies that different teaching approaches are necessary in medical and health sciences education. Although most learners preferred a unimodal approach in this study, multi sensory learning should be encouraged as it helps students to learn better and enhances memory retention. A consistently low verbal/linguistic score implies that there is a need to help medical and health sciences students to improve their English language proficiency whereas a lack of correlation between the interpersonal domain with any of the VARK subscale implies that non-conventional learning methods such as interprofessional learning or cooperative learning are necessary for the development of interpersonal skills among these students.